The Freedom to Choose to Marry - Colker, Ruth (Columbia Journal of Gender and Law, 2015)
Over the last several decades, the Lesbian, Gay, Bisexual, and Trans (LGBT)3 community made the political decision to push for “marriage equality” and the “freedom to marry,” rather than “same-sex” marriage or “homosexual” marriage.4 Like the decision that Justice Ruth Bader Ginsburg made in the 1970s, to refer to “gender-based” equality rather than “sex-based” equality, this change in terminology tried to focus society on the concept of “equality” rather than “sex”5 and the category of “marriage” rather than “homosexual marriage.”6 Although this change in terminology cannot, alone, account for changes in public opinion, it does coincide with increasing public acceptance of individuals having the freedom to marry the person they love without regard to sex or sexual orientation.7 Thus, when the Supreme Court announced its decision in Obergefell v. Hodges,8 the leading LGBT rights organizations applauded a victory for “marriage equality”9 or the “freedom to marry.”10 Partially reflecting this change in terminology, the Obergefell Court described the victory as one for “same-sex marriage,”11 the “freedom to marry,”12 and the “right to marry,”13 although it never mentioned the term “marriage equality.” But what is “marriage equality” and the “freedom to marry”? How does Obergefell relate to those two constitutional protections? This Article argues that the Obergefell decision reflects an important advance for some aspects of marriage equality and the freedom to marry,14 while also insufficiently developing the freedom to choose to marry. Nonetheless, the roots of the freedom to choose to marry can be found in the precedent underlying Obergefell as well as in some aspects of the decision itself.